Understanding India's business climate: a national business system perspective - Rangan, U. Srinivasa (Henry Stewart Talks, 2011)
Indian business climate, Growing business opportunity in India, National business system perspective, Institutions and policies, Indian political and legal systems, Strengths and weaknesses, India's human capital development system, Strengths and weaknesses, Indian financial system in transition, Corporate governance is a mix of Anglo-Saxon, German, and Japanese systems, Impact on companies, Legacy of India's interventionist trade, technology, and industrial policies, Challenges posed for foreign investors in India, How some foreign firms have dealt with India's difficult business climate, Examples of Honda, Vodafone, BP, Cairn, and Wal-Mart, Pepsi, GE, IBM, and Accenture, Indian firms as partners, BEL, Wipro, etc.